2015
DOI: 10.4103/0973-1482.140799
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoma rectum extending to para-rectal region

Abstract: Solitary plasmacytoma most commonly presents in bone (80%), while extramedullary plasmacytoma (EMP) is an uncommon (20%) entity that most commonly involves nasopharynx or upper respiratory tract. Involvement of the gastrointestinal tract occurs in approximated 10% of EMP cases, in that also solitary EMP of the rectum is an exceedingly rare entity. Here we are presenting a case of 55-year-old male patient who was diagnosed to have EMP of rectum in September 2012 who was initially operated in which de-bulking su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…6 Intraluminal disease can also present with symptoms mimicking other common gastrointestinal malignancies, such as microcytic anaemia, melaena, 7 haematochezia, 8 intussusception, 9 localised perforation 10 or tenesmus. 11 Table 1 details described presentations of intra-abdominal extramedullary plasmacytoma in the literature.…”
Section: Narrative Review Presentationmentioning
confidence: 99%
“…6 Intraluminal disease can also present with symptoms mimicking other common gastrointestinal malignancies, such as microcytic anaemia, melaena, 7 haematochezia, 8 intussusception, 9 localised perforation 10 or tenesmus. 11 Table 1 details described presentations of intra-abdominal extramedullary plasmacytoma in the literature.…”
Section: Narrative Review Presentationmentioning
confidence: 99%
“…For example, most scholars suggest that for lesions which are circumscribed and have a sufficiently large cut edge or a wide scope and a big tumor load, radiotherapy is difficult to achieve by a radical cure dose, and operation or added postoperative radiotherapy are reasonable choices for treatment. [17] Because the patient in this case was a young woman, and the tumor was located in the retroperitonea with a diameter > 10 cm, no affected regional lymph node was found during the surgery. As the radiation resistance of the tumor-adjacent organs was poor, the patient preferred surgical treatment that would reduce the tumor load while obtaining a clear pathological result.…”
Section: Discussionmentioning
confidence: 99%
“…The most common site is small intestine followed by stomach. [ 7 , 8 ] The incidence in colon is very rare, [ 9 , 10 ] especially in ileoceccal region is significantly low. Gabriel et al showed an extramedullaryileocecalplasmacytoma with a large ileocecal perforation.…”
Section: Discussionmentioning
confidence: 99%